(untitled) (Al-Qamar, 2022)
This research paper is a historical analysis of the Sindhi-Mohajir conflict in Sindh, since the creation of Pakistan to the end of the twentieth century. The paper argues that after independence in 1947 the influx of immigrants from India was officially diverted from Punjab to Sindh, resulting in a drastic ethnic transformation in the region. The increased number of Urdu-speaking immigrants with strong economic and political status caused sense of deprivation among the local Sindhi-speaking people. This deprivation paved the way for the ethnic political parties that gave rise to the ethnicity-based conflicts. The central argument claims that the Pakistan People’s Party (PPP) and Muttahida Qaumi Movement (MQM)’s politics played the most significant role in intensifying the Sindhi-Mohajir conflict in Sindh. To support this argument qualitative research method is used and the historical analysis is weaved with the help of secondary sources.